Prevalence of dental fluorosis and associated risk factors in 11-15 year old school children of Kanyakumari District, Tamilnadu, India: A cross sectional survey - Baskaradoss Jagan; Clement Roger; Narayanan Aswath (Wolters Kluwer Medknow Publications, 2008)
Objectives: This study presents data on the prevalence and severity of dental fluorosis in 11-15-years-old school children of Kanyakumari district, TamilNadu, India, and also the relationships between prevalence of dental fluorosis and selected risk factors. Materials and Methods: A total of 1800 children, from all the nine blocks of Kanyakumari district, studying in classes 6-10 were examined using type III examination. The assessment form designed specifically for this study was used while examining each student. Results: Dental fluorosis was present in 15.8% (285 children) of the study population and the community fluorosis index was calculated to be 0.27. The prevalence of dental fluorosis varied from as low as 1.4% in some blocks to as high as 29.4% in some others. There was a significant difference in the level of dental fluorosis between rural and urban residents ( P < 0.001). The prevalence of dental fluorosis was higher in children who consumed pipe water as compared to children who consumed ground water. 65% of the children with dental fluorosis had no caries, indicating the positive effects of fluoride. Conclusions: The prevalence of dental fluorosis can be attributed to the level of fluoride in the drinking water as it exhibited a step-wise increase when the water fluoride levels increased from 1.5-1.7 ppm. Measures for defluoridation of drinking water before distribution has to be taken in the high prevalence blocks to lower the burden of dental fluorosis in this community.